Ethical leadership, adhocratic culture, and innovative work behavior: Drivers of company performance - Estyana Puspita Aprilianty; Jati Waskito (Journal of Enterprise and Development (JED), 2023)
Purpose — This study aims to analyze the effects of ethical leadership and adhocratic culture on company performance, with innovative work behavior serving as a mediating factor.Method — This study employed a quantitative approach, with permanent employees from the Social Security Agency on Health (BPJS) company as survey respondents, constituting 70% of the sample. The sampling technique utilized purposeful saturation sampling. Validity and dependability of the outer model were evaluated using SmartPLS. The hypotheses were tested using the output of the SmartPLS inner model.Result — We found that ethical leadership and innovative work behavior have a significant influence on company performance. However, our analysis suggests that adhocratic culture does not exert a significant impact on company performance. In terms of the relationship between ethical leadership, adhocratic culture, and innovative work behavior, we observed that both ethical leadership and adhocratic culture play an important role in shaping innovative work behavior. However, our findings indicate that innovative work behavior does not serve as a positive and substantial mediator between ethical leadership and company performance. Similarly, we found that innovative work behavior does not act as a positive and substantial mediator between adhocratic culture and company performance.Contribution — This study makes an academic contribution by revealing the specific impacts of ethical leadership and adhocratic culture on company performance, highlighting the importance of ethical leadership and innovative work behavior.